Pengaruh Sanksi Perpajakan, Kesadaran, dan Kualitas Pelayan Pajak terhadap Penerimaan Pajak Bumi dan Bangun - Dudi Abdul Hadi; Mike Ayuni Lestari (Owner : Riset dan Jurnal Akuntansi, 2022)
Currently, taxes are the main source of government and state revenues that are used to finance government spending and national development. As one of the great potentials to support Regional Revenue, Land and Building Tax, will be the focus of this research. The  formulation of the problems studied in this study are: (1) Does tax sanctions affect land and building tax revenues. (2) Does awareness of taxpayers affect land and building tax revenues. (3) Does the quality of service affect land and building tax revenue. (4) Do tax sanctions, taxpayer awareness and service quality have a simultaneous effect on land and building tax revenues. The purpose of this study is to analyze the effect of tax sanctions, taxpayer awareness and quality of tax services on land tax revenues and. The independent variables used are tax sanctions, taxpayer awareness and quality of tax services. The dependent variable used is Land and Building Tax receipts from taxpayers. The method used in this study is quantitative, namely the procedure of research methods based on the philosophy of positivism, used to examine certain populations or samples, data collection using research instruments, data analysis is quantitative/statistical, with the aim of testing predetermined hypotheses. The analysis method of this research uses multiple linear regression. The results of this study indicate that tax sanctions, taxpayer awareness and quality of tax services have a positive and significant effect simultaneously on land and building tax revenues.